Aktivitas Siswa Mengikuti Kegiatan Pembelajaran Tatap Muka Terbatas Hubungannya Dengan Hasil Belajar Kognitif Mereka Pada Mata Pelajaran Pendidikan Agama Islam - Nisa Uswah Hasanah (Gunung Djati Conference Series, 2022)
The purpose of this study was to find out: 1) Students' activities in limited face-to-face learning, 2) Cognitive learning outcomes of students in the subject of Islamic Religious Education, 3) The relationship between students' activities participating in limited face-to-face learning with students' cognitive learning outcomes in Islamic Religious Education subjects . This study uses a quantitative approach and correlation method. Data collection techniques using observation, questionnaires, tests, interviews, and documentation. The data analysis techniques are: partial analysis and correlation analysis. The results showed that: 1) Student activity in limited face-to-face learning was in the high category, namely 3.81 2) Cognitive learning outcomes of students in the subject of Islamic Religious Education were in a very good category with an average value of 84.17 3) The relationship between student activity following face-to-face learning is limited with cognitive learning outcomes of students in the subject of Islamic Religious Education in the low category. Likewise with the results of the hypothesis test which shows that Tcount is 1.965 with 39 degrees of freedom with a significance level of 5% obtained Ttable of 1.701 indicating that Tcount is greater than Ttable, it can be concluded that (H0) is rejected and (Ha) is accepted, therefore there is the relationship between students' activities participating in limited face-to-face learning with their cognitive learning outcomes in Islamic Religious Education subjects.